KAJIAN SIFAT FISIK DAN KIMIA TANAH PADA AREAL PERTANAMAN SALAK (Salacca zalacca) di DESA PANGU KABUPATEN MINAHASA TENGGARA - Rifiani F. Woran; Ronny Nangoi; Jeanne E. Lengkong (COCOS, 2017)
ABSTRACTComparing physical and chemical properties of the soil in the salak (Salacca zalacca) plantation area of Pangu village and its relation to the growth and production of salak at various altitudes of 671 m asl, 512 m asl, and 400 m asl are the objectives of this study. The research was conducted in salak plantation of â‰¤ 10 years old at Pangu Village of South Minahasa Regency. Soil analyses of purposive sampling were conducted at the Laboratories of Soil and Soil Conservation Unit and of Soil Chemistry and Fertility Unit, Soil Science Department Agriculture Faculty UNSRAT Manado for 2 months (May to June 2017). Soil physical and chemical properties of all sites have relatively similar, ie.: sandy loam textures, more rapid permeability and low to moderate contents of N, P, K, and C-organic and moderately acidic soil pH. The reasons are similarity type of soils (Udepts of Inceptisols) in the study area. The soil fertility at altitude of 512 m asl is better than that of the other two altitudes, but the soil physical properties of 400 m asl and of 671 m asl are better than that of 512 m asl. Therefore, salak production in the three locations are more depending on the management of the plantation itself. Keywords : Physical Properties of Soil Chemistry and Salak Plant